A moda inclusiva em canais do youtube para pessoas com deficiência sensorial - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This research is part of term paper and seeks to understand the narrative used in fashion channels on YouTube, for people with disability, from a found problem, built through an exploratory research on the subject. For this, it was necessary to check how these narratives for accessible fashion are being developed in the vídeo platform and also the historical, social, cultural, technological and economic factors, so that the research had development. It seeks to provide a critical and grounded reflexion on the research topic, seeking to integrate value to Communicative Accessibility, Fashion Journalism and fashion as an instrument of communication and exploration of identity, so that a relationship could be made between the areas studied. Furthermore, states on the need for the media to include accessibility in the information transmitted to the public, so that people with disabilities have access to any type of content.
Keywords: Jornalismo sobre moda; Pessoas com deficiência; Integração social; Comunicação; Journalism about fashion; People with disabilities; CNPQ::CIENCIAS SOCIAIS APLICADAS